(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe knowledge, attitudes and practices of malaria prevention of cultivators and analyze some factors affecting malaria prevention practice of farmers in Ia Toi commune, Ia H’Drai district, Kon Tum province in 2022 Research method and time: The implementation period of the study was from January 2022 to the end of August 2022, with the participation of 230 people. Applying analytical cross-sectional research method. Using descriptive statistics to show the frequency, percentage of qualitative variables whilst statistical analysis was used with χ2, OR (95% CI) to test some factors associated to the study participants’ practices on malaria prevention with the significance level p<0.05. Results: The prevalence of people with appropriate knowledge and attitudes of malaria prevention was 84.3% and 78.7% respectively, the rate of good practices for malaria prevention was 71.7%. Some associated factors that contributed to the increase of the practices for malaria prevention of the study subjects included high education level, family history of having a patient with the disease, location far from the forest, home location far from rivers, streams and rivers, appropriated knowledge and attitudes on malaria preventions and being communicated on malaria preventions.